India : Technical Assistance Report-State of Tamil Nadu-Modernizing Budget Formulation and Managing Fiscal Risks. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2020)
Although Tamil Nadu's public financial management has been characterized by strong fiscal discipline to date, risks and challenges are emerging. The State has largely observed the Fiscal Responsibility Act targets on debts and deficit (25 percent and 3 percent to GSDP, respectively) except during the electricity bailout in 2016-17.1 However, these targets appear to have been met by (1) controlling and delaying expenditure, (2) underallocating mandated payments to various reserve funds, and (3) allowing off-budget borrowing by Public Sector Undertakings (PSUs). Accordingly, the State's borrowing capacity is restricted, leaving limited fiscal space to address high priority needs in education, health, electricity, roads, and water sectors, as well as to address growing infrastructure pressures. More than 63 percent of the State's spending on current items is committed, to salaries, pensions, and interest payments. Little room remains for additional borrowing to fund spending pressures; moreover, climate change is likely to exacerbate fiscal risks from water stress and natural disasters.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet